Zwiększenie stężenia D-dimerów podczas terapii kwasem traneksamowym i dyskusja na temat postępowania terapeutycznego w dziedzicznym obrzęku naczynioruchowym typu I - Özdemiral, Cansu; Cagdas, Deniz (Alergologia Polska - Polish Journal of Allergology, 2023)
Hereditary angioedema type 1 (HAE-1) is the most prevalent HAE type, and it results from decreased antigenic C1 inhibitor (C1-INH) levels or function. Bradykinin-mediated angioedema in the face, trunk, extremities, genitalia, gastrointestinal tract, and upper airway are the symptoms of this rare and potentially fatal disease. PD-C1-INH concentrates, recombinant C1-INH, tranexamic acid (TXA), danazol, icatibant, ecallantide, and fresh-frozen plasma (FFP) may be used for treatment. The focus of this article is to point out D-dimer elevation during TXA use. We detected d-dimer elevation incidentally in 2 patients with hereditary angioedema (HAE) type 1 during tranexamic acid (TXA) therapy, in whom elevations were normalized a week after suspended TXA. However, the TXA treatment is expected to decrease D-dimer levels in surgery and hyperfibrinolysis. On the other hand, although using TXA in long-term prophylaxis in HAE treatment is not recommended, we observed that 2 patients had significant reduction of their attack frequency for over a year.